Facile synthesis of platinum alloy electrocatalyst via aluminum reducing agent and the effect of post heat treatment for oxygen reduction reaction - Kang, Yun Sik; Yoo, Sung Jong; Lee, Myeong Jae; Kim, Mi-Ju; Lee, Stanfield Youngwon; Lee, Kug-Seung; Sung, Yung-Eun (PERGAMON-ELSEVIER SCIENCE LTD, 2016)
We have synthesized carbon-supported Pt and PtM (Au, Pd) nanoparticles (NPs) by using an aluminum (Al) metal foil as a reducing agent and conducted post heat treatments to investigate the relationship between oxygen reduction reaction (ORR) activity and surface crystalline/electronic structures of electrocatalysts. The as-prepared Pt and PtM (Au, Pd) NPs received the post heat treatment to induce structural modifications to improve ORR activity. From structural characterizations, well-synthesized carbon-supported Pt and PtM (Au, Pd) NPs were confirmed and the post heat treatment has the effect of inducing the alteration of surface crystalline structure and results in higher ORR activity. Furthermore, based on electrochemical characterizations, it is proved that after the heat treatment, the surface reconstruction brought about the increased fraction of Pt (111) and electrochemical active surface area of PtAu/C CO sample. And, the downshift of Pt d-band center of PtPd/C CO sample, which decreases the affinity of Pt to oxygen species, occurred resulting in more favorable kinetics of ORR. (C) 2016 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: GALVANIC DISPLACEMENT; SURFACE SEGREGATION; CATALYTIC-ACTIVITY; METHANOL OXIDATION; PT-SKIN; SHELL; ENHANCEMENT; DEPOSITION; STABILITY; POLYCRYSTALLINE